VMAT2 INHIBITOR COMPOUNDS AND COMPOSITIONS THEREOF - HETTINGER, Donald; HARRIOTT, Nicole; CULHANE, Jeffrey, C; BRANUM, Shawn (2023)
Provided is a compound selected from compounds of Formula (I) and pharmaceutically acceptable salts, solvates, and hydrates thereof: (I) wherein R1, R2, R3 and R4 are as defined herein. Such compounds are inhibitors of the vesicular monoamine transporter 2 (VMAT2) and have utility for treating, for example, neurological and psychiatric diseases and disorders. Also disclosed are compositions containing such compounds in combination with a pharmaceutically acceptable carrier, as well as methods relating to their use in subjects in need thereof.